The Statesman’s Year-Book Historical Companion - Paxton, John. author. aut Link
XI, 356 p.
Keywords: The Statesman's Year-Book Historical Companion is a companion to The Statesman's Year-Book to celebrate 125 years of annual publication, giving histories of countries, provinces and states from the 19th century and also acting as a name-change gazetteer.